Illustration of Java execution errors for beginner programmers - Sousa, Diogo Alexandre Rodrigues de (2020)
Programming is a subject that is learned by students all around the world. Many students encounter programming for the first time in introductory classes and face many new concepts they have never seen before. One of the main difficulties they encounter concerns understanding execution errors. Introductory classes do not address execution errors in a clear way that makes it easier for students to comprehend what they mean and how to avoid them. The Java stack trace is not easy to decipher without previous knowledge and experience on what each type of exception means and not specific enough for a beginner to pinpoint where the problem occurs. Several pedagogical programming tools exist that provide better explanations than the stack trace alone, taking leverage of variable roles and illustrations but neglecting exceptions in the process. The approach of this thesis was to develop a pedagogical tool that focused in providing explanations of execution errors. Using text and illustrations, the tool helps students by giving them better explanations of exceptions and facilitating the process of discovering what part of the code triggered the execution error. Roles of variables are also implemented, helping students by dividing variables into different use cases to better explain how they fit into the code. To determine whether the tool is effective, a study was carried out involving students in which they carried out some exercises to determine whether the tool is effective in assisting with execution errors.